A rare case of cervical tuberculous lymphadenitis followed by impaired consciousness. Issue 5 (September 2022) - Hirayama, Masatoshi; Nagata, Masashi; Yoshida, Ryoji; Nakamoto, Masafumi; Yuno, Akira; Maeshiro, Manabu; Fukuma, Daiki; Nakayama, Hideki
Abstract: Cervical tuberculous lymphadenitis (CTL) should always be considered as a differential diagnosis for cervical masses. CTL typically follows a chronic course and is rarely accompanied by systemic symptoms. Herein, we report a rare case of CTL as the initial manifestation followed by impaired consciousness. The patient was a 70-year-old woman who was referred to our department with a chief complaint of swelling of the left side of the neck. She had a family history of tuberculosis (TB). Seven days after her first visit, she presented with fever and a disturbance of consciousness and was taken to our emergency room. Initially, we suspected multiple metastases of malignant tumor and performed two biopsies of the cervical lymph nodes but could not reach a definitive diagnosis. Subsequently, histopathological examination of axillary lymph nodes showed findings that were characteristic of TB. In addition, Mycobacterium tuberculosis was detected from the specimen of cervical lymph nodes and spinal fluid by bacterial culture or polymerase chain reaction, which led to the definitive diagnosis of disseminated TB with CTL and tuberculous meningitis. Anti-TB therapy was administered, and a disturbance of consciousness and cervical lymphadenopathy improved without any neurological sequelae.